The development of massive open online course (MOOC) in traditionally taught course of emergency nursing among nursing students: a concept paper - Aung, Khin Thandar; Shaharom, Mohd Shahril Nizam; Abdul Razak, Rafiza (Asian Scholars Network (ASNet), 2019)
Education plays an important role in the development of a country and is only the bridge to create the better future of citizens. As technology is a very powerful tool in education, it provides new and innovative forms of support to teachers, students and the learning process more broadly. As web-based education and technology integration continue to increase, innovative approach to deliver online learning will also occur. One of the approach is Massive open online course (MOOC) and it is a technological based learning tool that is recently emerged in the higher educational landscape to provide additional learning opportunities for learners, teachers and educational institutions. The use of MOOCs in nursing education is currently under evaluated area of pedagogy, with only an emerging evidence base to support the wider integration into relevant undergraduate curricula. Although MOOCs have been available for almost a decade, and courses continually becoming available on commercial platforms, there remains a paucity of empirical evidence to support their utilization. Specifically, in nursing education, numerous roles for MOOCs have been proposed for both on- and off-campus learning, however, a clear rationale for their effective utilization is still nascent. This study aims to develop MOOC course and investigate the effectiveness of this integrated MOOC course of emergency nursing subject among nursing students. In addition, this study goes to identify the experiences of students and lecturers in this MOOC course. The course will be developed by applying the phases of Design Developmental Research (DDR) method such as phase 1- need analysis, phase 2- design and development, phase 3- implementation and evaluation. This study will contribute the critical thinking skills and innovative ideas among nursing students thus enhancing the students' learning abilities and equips the nursing students with innovation concepts and creative skills for an ever changing technologically-driven health care environment.